PENGARUH MARKETING MIX TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN MENGGUNAKAN METODE STRUCTURAL EQUATION MODELLING (SEM) - Syarah Widyaningtyas; Triastuti Wuryandari; Moch. Abdul Mukid (Jurnal Gaussian, 2016)
Marketing mix is a combination of variables that constitute the core of marketing system, consisting a set of variables that can be controlled and used by companies to influence consumer responses in target markets comprise. One that used in this study for analysis is Structural Equation Model (SEM). The study shows that satisfaction influenced by promotion, pricing, product and location of 38,9%, that loyalty is explained by satisfaction, promotion, pricing, product and location of 99,8%. In significant testing, it was found that pricing, product, location are significant to satisfaction. Satisfaction is significant to loyalty; while pricing, location, product are not significant to loyalty. Promotion is not significant to satisfaction and loyalty. Based on the results of data processing using software AMOS 22.0, the model SEM has been convenient and fit for use in research because the data has been proven to have normal distribution and have met the criteria for Goodness of Fit.Keywords: Marketing Mix, Consumer Satisfaction, Consumer Loyalty, Structural Equational Modelling.